Investigation into the built environment impacts on pedestrian crash frequencies during morning, noon/afternoon, night, and during peak hours: a case study in Miami County, Florida. Issue 9 (2nd September 2021) - Gu, Zongni; Peng, Binbin
Abstract: This study aims to investigate the effects of built environment factors on pedestrian crash frequency during the morning, noon-afternoon, night, and during peak hours. To accomplish this, micro-crash frequency models were developed based on the 2008–2011 Miami-Dade County pedestrian collision records collected from the Florida Signal Four Analytics (FSFA) dataset. Land uses evaluated in this study include educational, medical, recreational, commercial, residential, religious, and food establishment facilities. The negative binomial (NB) regression and zero-inflated negative binomial (ZINB) regression were employed to analyze the impacts of traffic volume, road design, and proportion of surrounding land use on road segments during different study periods. The results indicate that built environment factors are associated with different number of pedestrian collisions depending on the time of day/night. For example, pedestrian collisions associated with educational facilities are more frequent except after dark. Residential land use contributes to a significant and consistent increase in pedestrian collisions; while food establishment facilities land use shows an increase in pedestrian collisions during the noon/afternoon and night. As such, the specific and detailed findings in this study can help safety authorities carry out targeted transportation safety management and planning strategies to protect pedestrians in Miami-Dade County.